PENGEMBANGAN HOTS BERBASIS NEUROSAINS DALAM PEMBELAJARAN PAI - Siti Nur Sidah; Suyadi Suyadi (Piwulang: Jurnal Pendidikan Agama Islam, 2022)
For centuries, teachers have grown the brains of students witho rofession whose job is to change the brain every day. So it would be urgent if Islamic Religious Learning is linked with the science of the brain, through the development of neuroscience in Islamic education, because it is not the environment that changes students, but the motivation and character of the students themselves that can change behavior and even the environment, it can even be permanent. This research is a library research that uses content analysis as a technique in analyzing data. The results are relevant to tracing the traces of the mind and brain in the Qur'an.